The Impact of Medical Risk Perception on Patient Satisfaction: The Moderating Role of Shared Decision-Making - Zhou K; Chen L; Li M (Risk Management and Healthcare Policy)
Kairu Zhou,1,* Li Chen,2,* Min Li3 1School of Public Administration, South China University of Technology, Guangzhou, 510640, People’s Republic of China; 2Department of Clinical Research, Guangdong Second Provincial General Hospital, Guangzhou, 510317, People’s Republic of China; 3School of Business Administration, South China University of Technology, Guangzhou, 510641, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Li, School of Business Administration, South China University of Technology, Guangzhou, 510641, People’s Republic of China, Email bmminli@scut.edu.cnPurpose: The perception of medical risks is ubiquitous, influencing patients’ healthcare experiences, yet the “black box” of this influencing process is seldom explored. This study explores the relationship between medical risk perception, trust, and patient satisfaction while taking shared decision-making as a moderator.Methods: A stratified random sample of 450 inpatients from a tertiary public hospital in Guangzhou was selected for investigation, from June 2023 to September 2023. A moderated mediation model was tested using the PROCESS program, wherein medical risk perception was linked to patient satisfaction through trust, with shared decision-making acting as the moderating variable.Results: Medical risk perception had a significant negative predictive effect on patient satisfaction (β = − 0.383, p < 0.001), and after introducing the mediating variable, the negative predictive effect of medical risk perception on patient satisfaction remained significant (β = − 0.237, p < 0.001). Trust partially mediated the relationship between medical risk perception and patient satisfaction, with the mediating effect accounting for 37.86% of the total effect. The interaction term between medical risk perception and shared decision-making (β = 0.211, p < 0.001) significantly predicted trust.Conclusion: This study confirmed the mediating and moderating effects of trust and shared decision-making on the relationship between medical risk perception and patient satisfaction. The theoretical model constructed based on the theory of information asymmetry provides strategies and methods for healthcare managers to improve the quality of healthcare services and alleviate tensions in doctor-patient relationship.Keywords: medical risk perception, doctor-patient relationship, shared decision-making, trust, patient satisfaction